2018
DOI: 10.1080/17461391.2018.1448458
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the accuracy and reliability of body composition assessed with a handheld electrical impedance myography device

Abstract: The purpose of this study was to compare the body fat per cent (BF%) assessed with a unique handheld electrical impedance myography (EIM) device, along with other popular methods, to dual-energy X-ray absorptiometry (DXA). Participants included 33 males (aged 24.3 ± 4.6 years) and 38 females (aged 25.3 ± 8.9 years) who completed 2 visits separated by 24-72 h. The assessments included DXA, bioelectrical impedance analysis (BIA), skinfold measures (SKF), and three separate EIM measurements. No significant differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…To date, few studies have compared BF% assessed by the handheld Skulpt Chisel EIM device in comparison to DXA (Graybeal et al, ; McLester, ), reporting no significant total BF% differences between devices in active young adults and bodybuilders (EIM vs DXA BF% ranges: 23.43‐23.85% vs 23.33‐23.39%, respectively). Similarly, the current study also observed no significant differences in total BF% between the handheld Skulpt Chisel EIM device (24.09 ± 8.55%) and DXA (24.44 ± 7.15%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, few studies have compared BF% assessed by the handheld Skulpt Chisel EIM device in comparison to DXA (Graybeal et al, ; McLester, ), reporting no significant total BF% differences between devices in active young adults and bodybuilders (EIM vs DXA BF% ranges: 23.43‐23.85% vs 23.33‐23.39%, respectively). Similarly, the current study also observed no significant differences in total BF% between the handheld Skulpt Chisel EIM device (24.09 ± 8.55%) and DXA (24.44 ± 7.15%).…”
Section: Discussionmentioning
confidence: 99%
“…To date, few studies have compared BF% assessed by the handheld Skulpt Chisel EIM device in comparison to DXA (Graybeal et al, 2018;McLester, 2018), reporting no significant total BF% differences between devices in active young adults and bodybuilders (EIM vs DXA BF% ranges: 23.43-23.85% vs 23. 33-23.39%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This discrepancy between the two measurements leads to the questioning of which device is more precise. The Skulpt Chisel was found to be an accurate and reliable method for EIM measurements [6]. In practice, bioelectrical impedance analysis, such as that performed by the Bodystat Multiscan 5000, can overestimate fat-free mass and under estimate fat mass and body fat percentage [7].…”
Section: Discussionmentioning
confidence: 99%